Flexible hard−soft carbon heterostructure based on mesopore confined carbonization for ultrafast and highly durable sodium storage. (5th March 2023) - Qiu, Guojian; Ning, Meng; Zhang, Minglu; Hu, Junqi; Duan, Zhihua; Cheng, Dejian; Miao, Lei; Li, Zhenghui; Zhang, Haiyan
Abstract: Despite great progress in sodium-ion battery, exploiting carbonaceous anodes incorporating large capacity, high rate performance and long-term cycling stability is still a big challenge. In this work, novel heterostructured, hollow hard−soft carbon spheres are designed by mesopore confined carbonization. The results show that the confined carbonization makes the carbon layers spontaneously arrange in different levels, resulting in the formation of nanometer-scale, interwoven hard and soft carbon domains. Moreover, the unique composite carbon layers provide a flexible and breathable shell capable of maintaining nanostructure during long-term repeated charge/discharge processes. As such, the hard−soft carbon heterostructure is able to deliver a capacity >240 mA h g −1 under a current density of 1 A g −1 . Even with an ultralarge current density of 30 A g −1, the capacity remains 104 mA h g −1, demonstrating a very short Na output time of 12.5 s. Moreover, the hard−soft carbon heterostructure shows no dramatic capacity loss during a long-term repeated charge/discharge tests over 10, 000 cycles, showing a very low capacity loss rate of 0.0026% per cycle. As far as is known, such high-rate capability and outstanding cycling durability has been rarely achieved before. Graphical abstract: Image 1 Highlights: Heterostructured, hollow hard−soft carbon spheres are designed. The heterostructured carbon has flexible skeleton with superior structural stability. The obtained carbon can withstand an ultrafast Na storage of 30 A g −1 . Very low capacity loss rate of 0.0026% per cycle during long-term cycling test over 10, 000 cycles.